Qatar’s Path to a Knowledge-Based Economy: A Content Analysis of Entrepreneurship Training Initiatives - Gangi, Yagoub Ali; Idris, Alfadil Timan (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">In its pursuit of economic diversification and the transformation towards a knowledge-based economy, Qatar has acknowledged the pivotal role of entrepreneurship as a driving force for innovation and economic advancement. This study presents a content analysis endeavour that delves into the significance of entrepreneurship training in shaping Qatar’s journey towards the knowledge-based economy. By examining aspects such as program design, content, trainer profiles, and teaching methodologies within entrepreneurship training programs, this investigation aims to uncover the influence of these initiatives on Qatar’s strategy for economic diversification. Notably, the research findings underscore a dominance of entrepreneurial and business management skills in the content of entrepreneurship training, while academic trainers employing traditional educational methods are prevalent among training institutions. Against the backdrop of entrepreneurship training preceding formal education, this research endeavours to illuminate the roles played by entrepreneurship skills, business and management expertise, and innovation capabilities in elevating Qatar’s competitive stance and fostering a knowledge-driven economy. This inquiry addresses a research gap by responding to the limited literature concerning the intersection of training and knowledge economy within the Gulf Cooperation Council (GCC) region. Through meticulous content analysis and insights drawn from prior research, the study offers substantiated perspectives that can inform the development and refinement of forthcoming entrepreneurship training programs. This research initiative enriches the expanding knowledge reservoir by providing a comprehensive comprehension of the alignment between entrepreneurship training and Qatar’s ambitions for a competitive knowledge-based economic landscape.